Nilai-Nilai Tarbiyah dalam Tarekat Syadziliyah - M. Mudlofar (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
The development of science and intellectuality in the Islamic world has fluctuated. This coincides with the ebb and flow of the East-West socio-political world. Seeing such scientific conditions and intellectual positions, Muslim thinkers moved to take a stand. Efforts to formulate Islamic education continue. The goal is to find the right formula on how to broaden the intellectual insight of Muslims while still having a high commitment to Islamic aqidah. One of the Muslim thinkers who concentrated on this effort was al-Syadzili. On the basis of the above phenomena, researchers are interested in studying al-Syadzili's thoughts related to education. This research is classified as library research, namely, a study that relies on data and information sourced from books or literature. This kind of analysis is useful for understanding the overall concept of the object being studied. In building tarbiyah (educational) values, Sheikh al-Syadzili described them in three concepts, namely through; (a) the concept of Sufism, (b) the concept of tarekat, and (c) the concept of ubudiyah. In al-Syadzili's view, Sufism has the ability for a person to get closer to Allah, the tarekat is a way for someone to achieve the goal of getting closer to Allah (taqarrub ilallah), meanwhile, ubudiyah is a bridge for one's obedience to orders and away from Allah's prohibitions. With these three concepts, tarbiyah (education) values ​​will be obtained framed by the teachings of the Syadziliyah tarekat, among others, (a) the value of faith education, (b) the value of practical education, (c) the value of scientific education, (d) the value of education morals, and (e) the value of social education.